Personality and Organizational Citizenship Behavior: How Transformational Leadership Plays a Moderating Role: Study at a Tourism Services Company in Malang - Zaidan Nazih; Ikhsan Maksum (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
Organizational Citizenship Behavior (OCB) refers to supplementary actions performed by individuals to enhance organizational efficiency. This study investigates the correlation between personality traits and organizational citizenship behavior influenced by transformational leadership. Organizational Citizenship Behavior (OCB) is crucial in enhancing corporate success. This research employs a quantitative methodology inside an exploratory framework. The study population comprised 92 employees of the Tourism Services Company in Malang. The employed sample technique is saturation sampling. The data collection approach employs a questionnaire. The data analysis process employs SmartPLS 4.0 software, integrating external model assessment, internal model evaluation, and hypothesis testing. The study's results indicated a significant and positive connection between personality and organizational citizenship behavior, evidenced by a T-table value of 1.96 and a P-value of 0.000 below 0.05. The moderation test results demonstrate that transformational leadership adversely moderates the link between personality and OCB, indicated by a statistical value of -0.219, less than the T-table value of 1.96, and a P-value of 0.827, exceeding 0.05. This study demonstrates that organizational citizenship behavior (OCB) evolves through employee knowledge, independent of leadership direction. This study investigates the relationship between personality and organizational citizenship behavior, mediated by transformational leadership.  Organizational Citizenship Behavior (OCB) is crucial for enhancing organizational effectiveness. This research employs a quantitative approach utilizing exploratory techniques. The study's population comprised 92 employees of the Tourism Services Company in Malang. The employed methodology is extensive sampling. The employed data collection method is a questionnaire. The employed data analysis approach is SmartPLS 4.0 software, encompassing an outer model, an inner model, and hypothesis testing. The research findings indicate a considerable and significant impact of personality on Organizational Citizenship Behavior (OCB), demonstrated by a T-table value of 1.96 and a P-value of 0.000, below 0.05. The moderation test results demonstrate that transformational leadership negatively moderates the relationship between personality and organizational citizenship behavior, as indicated by a statistical value of -0.219, below the T-table threshold of 1.96, and a P-value of 0.827, which exceeds 0.05. This study demonstrates that organizational citizenship behavior (OCB) evolves through employee knowledge, irrespective of the leader's guidance. Transformational leadership does not enhance organizational citizenship behavior, as employees possess a comprehensive awareness of assisting colleagues and the organization independently of the leader's directives.